Peer Mentoring sebagai Metode Pembelajaran Komunikasi untuk Mahasiswa Kedokteran - Florettira, Mutiara Tri; Syakurah, Rizma Adlia (HIGEIA (Journal of Public Health Research and Development), 2021)
First year medical students have difficulty adapting to higher education levels. Peer mentoring could be support to adapt, especially to communication skills. This study aimed to evaluate communication learning methods for medical students through peer mentoring. A descriptive observational with cross-sectional study design was used and 234 medical students were participated. Respondents in the first year and the first month were divided into 32 groups, with 6-7 member to interview clinical clerkship students and their group mates. Majority of respondents considered these activities important and beneficial for the adaptation process. The majority of respondents (99.6%) considered it important to interview group mates to know their friends. The majority of clinical students as mentors (96.9%) considered this activity useful to evaluate themselves and help them communicate better. There is a reciprocal relationship between first-year medical students as mentees and clinical students as mentors. Both mentors and mentees consider peer mentoring as a method of learning communication to have many benefits. Peer mentoring can be developed for medical students, not only first-year medical students. Keywords: Peer Mentoring, Communication Learning, Medical Students